2022
DOI: 10.3889/oamjms.2022.10302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methanol Concentration on the Extraction of Moringa Leaf (Moringa oleifera) and Papaya Fruit (Carica papaya) on Elastase and Hyaluronidase Installing Activities

Abstract: Abstract BACKGROUND OF THE STUDY: Β-carotene, flavonoids and phenolic compounds found in methanol extracts of Moringa leaves and papaya fruit have high antioxidant activity so that they can be used for antiaging. The concentration of solvent is a factor that will affect the levels of active ingredients in methanol extract. This study aims to determine the effect of the concentration of the methanol solvent derived from the extraction of Moringa leaves and papaya fruit on the inhibitory activity of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…These results were consistent with those of researchers [23] who reported that 70% methanol solvent was the most effective solvent concentration to inhibit the enzymes elastase and hyaluronidase in moringa leaf methanol extracts. This destroys the aerobic bacteria in the egg shell.…”
Section: Egg Loss % At Different Period Of Storage Among Different Co...supporting
confidence: 93%
“…These results were consistent with those of researchers [23] who reported that 70% methanol solvent was the most effective solvent concentration to inhibit the enzymes elastase and hyaluronidase in moringa leaf methanol extracts. This destroys the aerobic bacteria in the egg shell.…”
Section: Egg Loss % At Different Period Of Storage Among Different Co...supporting
confidence: 93%